2012
DOI: 10.1002/pen.22185
|View full text |Cite
|
Sign up to set email alerts
|

Drawing and ultimate tensile properties of nylon 6/nylon 6 clay composite fibers

Abstract: This study systematically investigated the drawing and ultimate tenacity properties of the Nylon 6 (NY6)/nylon 6 clay (NYC) composite fiber specimens prepared at varying NYC contents and drawing temperatures. The achievable draw ratio (Dra) values of NY6x(NYC)y as‐spun fiber specimens initially increase in conjunction with NYC content, and then approach a maximum value, as their NYC contents and drawing temperature approach the 0.5 wt% and 120°C, respectively. The percentage crystallinity (Xc) values of NY6x(N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Steinmann et al determined the influence of nano‐phyllosilicates on the drawability of nylon 6 filaments . The drawing behavior and ultimate tenacity of the nylon 6/NYC composite fibers prepared by varying NYC contents and drawing temperatures were systematically investigated by Yeh et al.…”
Section: Introductionmentioning
confidence: 99%
“…Steinmann et al determined the influence of nano‐phyllosilicates on the drawability of nylon 6 filaments . The drawing behavior and ultimate tenacity of the nylon 6/NYC composite fibers prepared by varying NYC contents and drawing temperatures were systematically investigated by Yeh et al.…”
Section: Introductionmentioning
confidence: 99%
“…These results clearly indicate that the improvement of molecular orientation along the drawing direction, the development of more ordered crystalline structure, and the increase in crystallinity, have a positive influence on the mechanical properties of PA 5,6 fibers when subjected to the drawing process. 6,25…”
Section: Resultsmentioning
confidence: 99%
“…4 Since this work, many studies have been carried out to investigate the effect of drawing of PA fibers on the structure and mechanical properties. 512 However, up to now, only a few studies have been reported on the polyamide 5,6 (PA 5,6). Puiggalí et al.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage crystallinity values of the specimens were calculated using the equation belowwhere ΔHm0 is the enthalpy of melting if the PA6 polymer is 100% crystalline, Δ H c is the measured enthalpy of crystallization and φ corresponds to the weight fraction of HPCP in PA6 matrix. According to the literature [18], ΔHm0 was reported to be 230 J/g.…”
Section: Methodsmentioning
confidence: 99%